REPRESENTASI PEREMPUAN DAN RELASI KEKUASAAN PADA CERPEN RUMAH-RUMAH NAYLA KARYA DJENAR MAESA AYU - Lia Metha Sevita Ika Sulistiyarini; Asropah (STKIP Subang, 2024)
This article aims to analyze the short story Rumah-Rumah Nayla by Djenar Maesa Ayu, featured in the collection Kasur Tanah Cerpen Pilihan Kompas 2017, using Sara Mills' critical discourse analysis approach. The story presents a complex representation of women through the main character, Nayla, who undergoes an identity shift from being a wife in an